Ruling the rûaḥ: Emotional Experience and Expression in Ancient Hebrew - Atwood, Joel (The Biblical Annals, 2022)
Emotions are one of the most fascinating and difficult aspects of human experience, and have received significant attention in biblical studies. This paper explores how one Hebrew lexeme, rûaḥ, provides a point of entry into the complex world of how emotions are expressed in ancient texts. Drawing from some insights of Cognitive Linguistics, it examines the use of rûaḥ to express the experience of impatience and patience, and arrogance and humility. This paper then challenges a long-held but simplistic equation of rûaḥ with anger, and argues that a more nuanced and complex relationship exists between lexeme and emotion than most citations in scholarship suggest.